PREDICTING PRECLINICAL THROMBOGENIC ABNORMALITIES IN PATIENTS WITH ESSENTIAL ARTERIAL HYPERTENSION - S. S. Bunova; L. P. Firstova; A. V. Nelidova; E. V. Usacheva (Кардиоваскулярная терапия и профилактика)
Aim.To identify early (preclinical) markers of thrombogenic abnormalities in patients with essential arterial hypertension (EAH).Material and methods. The study included 137 EAH patients, aged 30–60 years. The parameters of both coagulation and platelet haemostasis were assessed.Results. In patients with EAH and obesity (O), the following parameters were elevated: activated partial thromboplastin time (aPTT); fibrinogen; and soluble fibrin monomer complex (SFMC). In EAH patients without O, the levels of spontaneous platelet aggregation were elevated. Among overweight patients, the levels of adreno-reactivity were associated with leptin levels (rs=0,8; р=0,007). In obese patients, there was a significant correlation between insulin and leptin levels (rs=0,7; р=0,0049). The correlation analysis of the neurohumoral and haemostatic parameters demonstrated an association between leptin and SFMC levels (rs=0,8; р=0,0007). In EAH patients, the changes in neurohumoral profile are linked to increased body mass, elevated levels of insulin (Н=9,6; р=0,0082), leptin (Н=12,1; р=0,0024), and adreno-reactivity (Н=8,8; р=0,0122).Conclusion. In patients with EAH and O, the observed haemostatic abnormalities could be characterised as hypercoagulation syndrome. The findings obtained suggest that fibrinogen and SFMC could be regarded as early markers of thrombosis development in patients with EAH and O. Therefore, these parameters can be used in the screening programme, in order to identify the individuals with abnormalities of coagulation haemostasis and fibrinolysis.